Plyometric training in female athletes. Decreased impact forces and increased hamstring torques - Hewett, T. E.; Stroupe, A. L.; Nance, T. A.; Noyes, F. R. (The American Journal of Sports Medicine, 1996)
Hewett et al (1) examined the effects of a plyometric training program on landing mechanics and leg strength in female athletes involved in jumping sports. The plyometric program was designed to decrease landing forces by helping the athletes learned neuromuscular control over the lower extremity during landing. It was also designed to increase vertical jump height. FINDINGS: Peak landing forces during a volleyball block jump decreased by 22%. Horizontal forces acting upon the knee during landing were reduced by around 50%. Hamstring-quadriceps peak torque ratios increased 26% on the nondominant leg and 13% on the dominant leg. Hamstring power increased 44% on dthe ominant leg and 21% on the nondominant leg. Mean vertical jump increased by 10%. IMPLICATIONS: A properly performed plyometric training protocol may help prevent knee injury in female athletes involved in jumping sports such as volleyball by increasing knee stabilization during landing and teaching athletes muscular control. Plyometrics may also help correct torque imbalances between the hamstrings and quadriceps and can help increase vertical jump height.